Giving fish or teaching fishing? the impact of China’s foreign aid on digital service trade in belt and road initiative countries - Rongsheng Tang; Zewen Xiao; Xue Zhong (Digital Economy and Sustainable Development)
Abstract This paper empirically analyzes the relationship between China’s foreign aid and the digital service trade of Belt and Road Initiative (BRI) countries, using panel data from 2005 to 2017. We find that under the framework of the BRI, China’s foreign aid has a significantly positive impact on the digital service exports of recipient countries. This positive effect remains robust after addressing potential endogeneity concerns and conducting various robustness checks. Furthermore, the analysis reveals that Other Official Flows(OOF) is more effective than Official Development Assistance(ODA) in enhancing the digital service exports of recipient countries. Moreover, the positive impact of China’s foreign aid is particularly pronounced in high-income countries compared to middle- and low-income countries. Additionally, industry-level heterogeneity analysis shows that China’s foreign aid significantly promotes the export of “other business services.” In contrast, its impact on other industries is less evident. Finally, mechanism analysis indicates that the promotion of digital service exports by China’s foreign aid primarily operates through improvements in human capital and institutional quality in recipient countries.